EFEKTIFITAS ESKTRAK PUTRI MALU, BAWANG PUTIH, DAN LENGKUAS TERHADAP PENYAKIT KARAT PUTIH (Puccinia horiana Henn.) PADA PEMBIBITAN TANAMAN KRISAN (Chrysanthemum sp.) - Sandra O. K. Kalrengsang; Bernadeth V. Montong; Max M. Ratulangi (COCOS, 2022)
ABSTRACTChrysanthemum (Chrysanthemum sp.) is an ornamental plant that produces flowers that havehigh economic value. Chrysanthemum flowers have the potential to be developed because they are ingreat demand by the public in terms of beautiful shapes and colors. One of the important stages inchrysanthemum cultivation is seeding. The main problem in chrysanthemum farming is the attack ofwhite rust caused by a fungus (P. horiana) starting from seedling to harvesting. The use of plantextracts as alternative pesticides has many advantages and benefits. Plants that have the potential tobe used as botanical pesticides include mimosa, garlic and galangal. This study aims to determine theeffectiveness of giving the extracts of mimosa, garlic and galangal in chrysanthemum plant nurseriesto suppress white rust disease caused by the fungus P. horiana. This research was carried out usingan experimental design, namely a completely randomized design (CRD) which consisted of 4 (four)treatments and 4 replications, namely K (control), P1 (20% mimosa extract), P2 (20% garlic extract),and P3 (20% galangal extract). Based on the results of observations of the symptoms of white rust (P.horiana) the upper surface of the leaves at first in the form of yellow spots which gradually changedcolor to dark brown, then on the lower surface of the leaves can be seen the presence of pustules thatare pink, and long Over time the pustules will get bigger and then turn white. The highest percentageof attacks was in the control (K) 10.08%, the garlic extract treatment 20% (P2) 4.27%, then followedby the 20% galangal extract treatment (P3) 3.33%, and the mimosa extract treatment 20% (P1)0.96%. The results showed that the use of extracts of Putri malu, garlic and galangal was able tosuppress white rust disease (P. horiana) in chrysanthemum plant nurseries, with the best treatment insuppressing white rust disease (P. horiana) which was mimosa extract 20% (P1 ) with attackpercentage : 0.96%, followed by galangal extract (P3) : 3.33% and garlic extract (P2) : 4.27%. Inaccordance with the results of the research that has been carried out, it is necessary to carry outfurther research on the use of Mimosa Extract, Garlic and Galangal against white rust (P. horiana) inchrysanthemum plant nurseries with higher concentrations and in other varieties of chrysanthemumseedlings.Keyword : effectiveness, extract, mimosa, garlic, galangal, chryns, white rust disease